Acute Hepatic Failure as a Leading Manifestation in Exertional Heat Stroke - Qi Jin; Erzhen Chen; Jie Jiang; Yiming Lu (Case Reports in Critical Care)
Background. Acute hepatic failure (AHF) is uncommon as a leading symptom in patients with exertional heat stroke (EHS). Which stage to perform the liver transplantation for severe hepatic failure in EHS is still obscure at clinical setting. The conservative management has been reported to be successful in treating heat-stroke-associated AHF even in the presence of accepted criteria for emergency liver transplantation. Case Presentation. Here, we reported a 35-year-old male who presented with very high transaminases, hyperbilirubinemia, significant prolongation of the prothrombin time, and coma. No other causes for AHF could be identified but physical exhaustion and hyperthermia. Although the current patient fulfilled London criteria for emergency liver transplantation, he spontaneously recovered under conservative treatment including intravenous fluids, cooling, diuretics as mannitol, and hepatocyte growth-promoting factors. Conclusions. Meticulous supportive management could be justified in some selected cases of AHF due to EHS.